Fundamentos jurídicos para establecer limitaciones al derecho de procreación y proteger el interés superior del niño, Perú 2024 - Santillan Gonzales, Mauro Roberto (2025)
The present research addressed a social issue that significantly impacts the best interests of the child in Peru: indiscriminate procreation. This situation stems from the absence of the State in certain regions and the lack of institutional policies aimed at regulating and reducing the gaps associated with this problem. The constant evolution of the family structure has led to a deeper analysis of the rights of its current and future members, particularly regarding the legal implications of procreation. When exercised without planning, this right can result in serious consequences such as abandonment, helplessness, and lack of protection for children. Therefore, the main objective of this study was to identify the legal foundations for establishing limitations on the right to procreation in order to safeguard the best interests of the child. The research employed a basic exploratory methodology, combining dogmatic legal analysis with a sociological-functional approach. As a result, it was possible to determine that constitutional principles support the need to regulate this right, emphasizing that procreation should be exercised responsibly and within a legal framework that ensures the protection of fundamental rights.